2019
DOI: 10.1177/1526602819851202
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Particle Imaging–Guided Stenting

Abstract: Purpose:To assess the feasibility of magnetic particle imaging (MPI) to guide stenting in a phantom model. Materials and Methods: MPI is a new tomographic imaging method based on the background-free magnetic field detection of a tracer agent composed of superparamagnetic iron oxide nanoparticles (SPIOs). All experiments were conducted on a custom-built MPI scanner (field of view: 29-mm diameter, 65-mm length; isotropic spatial resolution 1–1.5-mm). Stenosis phantoms (n=3) consisted of polyvinyl chloride (PVC) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 42 publications
0
36
0
Order By: Relevance
“…Several commercially available SPIONs have been studied as MPI tracers. Ferucarbotran (an off-brand version of Resovist ® ) is a commercially available SPION contrast agent developed specifically for MRI that is commonly used for MPI studies 13 , 14 . However, it has been suggested that only 3% of the total iron mass from Resovist ® contributes to the MPI signal due to particle-particle interaction within carboxydextran coated core 1 .…”
Section: Introductionmentioning
confidence: 99%
“…Several commercially available SPIONs have been studied as MPI tracers. Ferucarbotran (an off-brand version of Resovist ® ) is a commercially available SPION contrast agent developed specifically for MRI that is commonly used for MPI studies 13 , 14 . However, it has been suggested that only 3% of the total iron mass from Resovist ® contributes to the MPI signal due to particle-particle interaction within carboxydextran coated core 1 .…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to CT and MRI, the stent lumen can be assessed without artifacts in MPI [ 8 ]. Recently, Herz et al demonstrated the potential of MPI to guide percutaneous transluminal angioplasties of vascular stenoses [ 9 ]. Since both, MPI and MRI use oscillating magnetic fields, the heating of metallic objects is a potential risk that needs to be investigated more closely.…”
Section: Introductionmentioning
confidence: 99%
“…This means that MPI is a high signal to noise ratio (SNR) imaging platform like nuclear medicine [24,31]. MPI has demonstrated promise for applications such as angiography [32,33], stem cell tracking [34][35][36], brain perfusion [37,38], lung perfusion [39], lung ventilation [40,41], cancer imaging [42], gut bleed detection [43], remote magnetic actuation and magnetic catheter steering and guidance [44][45][46][47], and localized MFH [21,22,48,49]. Selected MPI images are shown in Figure 1.…”
Section: Advantages Of Mpi Among Other Imaging Modalitiesmentioning
confidence: 99%